2023
DOI: 10.1088/1748-9326/acd8d3
|View full text |Cite
|
Sign up to set email alerts
|

On the role of antecedent meteorological conditions on flash drought initialization in Europe

Abstract: The fast depletion of soil moisture in the top soil layers characterizes flash drought events. Due to their rapid onset and intensification, flash droughts severely impact ecosystem productivity. Thus understanding their initialization mechanisms is essential for improving the skill of drought forecasting systems. Here, we examine the role of antecedent meteorological conditions that lead to flash droughts across Europe over the last 70 years (1950--2020) using ERA5 dataset. We find two major flash-drought typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Notably, the majority of events were associated with the Antecedent-concurrent Prec type (Cluster 2), the Antecedent Tem-concurrent Prec type (Cluster 3), or the Antecedent Tran-concurrent Prec type (Cluster 4). This emphasizes the pronounced influence of antecedent conditions in shaping the dynamics of flash drought occurrences (Shah et al, 2023). In addition, some flash drought events were only driven by the Concurrent Prec type (Cluster 1), indicating the crucial role of concurrent Prec deficit in flash drought occurrences (Koster et al, 2019).…”
Section: Classification Of Flash Drought Eventsmentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, the majority of events were associated with the Antecedent-concurrent Prec type (Cluster 2), the Antecedent Tem-concurrent Prec type (Cluster 3), or the Antecedent Tran-concurrent Prec type (Cluster 4). This emphasizes the pronounced influence of antecedent conditions in shaping the dynamics of flash drought occurrences (Shah et al, 2023). In addition, some flash drought events were only driven by the Concurrent Prec type (Cluster 1), indicating the crucial role of concurrent Prec deficit in flash drought occurrences (Koster et al, 2019).…”
Section: Classification Of Flash Drought Eventsmentioning
confidence: 88%
“…This trend implies a potential amplification of vegetation water consumption's role in influencing the occurrence of flash droughts (Guo et al, 2023). These results imply a growing influence of antecedent conditions, particularly antecedent temperature and transpiration (Shah et al, 2023). Subsequently, we analyzed the spatial patterns of trends for each identified cluster with a 15-year moving window (Figure 9).…”
Section: Spatio-temporal Evolution Of Mechanisms Of Flash Drought Onsetmentioning
confidence: 99%
“…In addition, we used 0-1 m soil moisture, which is critical for both surface evaporation and root zone vegetation transpiration, to identify grids under drought conditions. However, the definition is not sensitive to the choice of 0-1 m soil moisture or total column soil moisture according to previous work (Shah et al 2023. Finally, this study includes small to large scale drought events to provide a comprehensive comparison across spatial scales and between 1D and 3D methods.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that flash droughts occur most frequently in central and eastern Europe (Shah et al, 2022;Sungmin & Park, 2023) and have become more common across all of Europe, with many areas experiencing at least an 80% increase in flash drought frequency from 1950-1984(Shah et al, 2022. Shah et al (2023) also identified two types of flash drought development across Europe. The first is associated with a decline in precipitation combined with increased evaporative demand, while the second type is associated with high precipitation preceding the event start, followed by an immediate precipitation deficit.…”
Section: Europementioning
confidence: 96%